Correction: Removal of emerging contaminants by pre-mixed PACl and carbonaceous materials. Issue 47 (27th May 2015) - Jiang, W.; Xiao, F.; Wang, D. S.; Wang, Z. C.; Cai, Y. H.
<x xml:space="preserve">Abstract</x> Correction for 'Removal of emerging contaminants by pre-mixed PACl and carbonaceous materials' by W. Jiang et al., RSC Adv., 2015, 5, 35461–35468.